Highly efficient and reversible CO2 capture by tunable anion‐functionalized macro‐porous resins. Issue 7 (27th January 2017) - He, Xi; Mei, Ke; Dao, Rina; Cai, Jingsong; Lin, Wenjun; Kong, Xueqian; Wang, Congmin
Abstract : Anion functionalized strategy has been proposed for the synthesis of macro‐porous resins [IRA‐900][An] through the neutral reaction of the basic resin [IRA‐900][OH] with the corresponding donors. Combining CO2 adsorption results and FT‐IR, solid‐state 13 C NMR characterization as well as quantum chemical calculations, chemical adsorption mechanism was verified and tunable capture of CO2 was realized. Among them, the anion functionalized resin [IRA‐900][Triz] exhibits an extremely high adsorption capacity (4.02 mmol g −1 at 25°C, 0.15 bar), outperforming many other good adsorbents. Finally, we discuss the thermostability and recycling stability of [IRA‐900][Triz], which shows a great potential in the industrial capture of CO2 . © 2017 American Institute of Chemical Engineers AIChE J, 63: 3008–3015, 2017